Chromogenic culture media complements diagnostic cytology in the visual identification of pathogenic skin bacteria in dogs and cats - Avberšek, Miha; Ihssen, Julian; Faccio, Greta; Spitz, Urs; Cugmas, Blaž (Frontiers in Veterinary Science, 2023)
In dogs and cats, bacterial skin infections (pyoderma and otitis externa) are a common cause for visiting the veterinary clinic. The most frequent skin pathogens are Staphylococcus pseudintermedius, Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa, often requiring different therapeutic antibiotic protocols. Unfavorably, existing diagnostics based on cytology cannot reveal bacterial species but only bacterial shapes such as cocci or rods. This microscopic limitation could be overcome by clinical translation of affordable chromogenic media, which enable species identification based on bacterial colonies growing in different colors and sizes. In this study, we determined how well inexperienced general veterinary clinicians identified bacterial pathogens from the skin and ears on two commercial (Chromatic™ MH and Flexicult® Vet) and one custom-made Mueller Hinton agar-based chromogenic medium. For this purpose, four veterinarians evaluated 100 unique samples representing ten bacterial species. On average, clinicians correctly identified between 72.1% and 86.3% of bacterial species. Colony colors developed quickly on the Chromatic™ MH medium, leading to the highest 81.6% identification accuracy after 24h incubation. However, Flexicult® Vet exhibited the highest accuracy of 86.3% after prolonged 48h incubation. Evaluators easily recognized bacteria displaying uniquely colored colonies like green-brown Pseudomonas aeruginosa, blue Enterococcus faecalis, orange-brown Proteus spp., and red Escherichia coli. Oppositely, staphylococci shared uncharacteristically pale pink colonies causing misidentifications among the genus, deteriorating overall accuracy by around ten percentage points (from 90.9%). Another reason for identification errors was the evaluators’ inexperience, reflected in not recognizing colony size differences. For example, although Streptococcus canis exhibited the tiniest colonies, the species was frequently mistaken for other cocci. Finally, around 10% of errors were negligence-related slips due to unconsidered sample history. To conclude, the introduction of chromogenic media into veterinary clinics can significantly complement diagnostics in skin inflammations by identifying pathogen species in around 80% of cases. The extra information may help in therapeutic dilemmas on antibiotics and standard antimicrobial susceptibility testing. Additional personnel training and evaluation help by visuals, flowcharts, checklists, and, if necessary, microbiologists could further improve identification accuracy.